Reactivity, stability, and strength performance capacity in motor sports. Issue 11 (1st September 2006) - Baur, H; Müller, S; Hirschmüller, A; Huber, G; Mayer, F
Abstract : Background: Racing drivers require multifaceted cognitive and physical abilities in a multitasking situation. A knowledge of their physical capacities may help to improve fitness and performance. Objective: To compare reaction time, stability performance capacity, and strength performance capacity of élite racing drivers with those of age-matched, physically active controls. Methods: Eight élite racing drivers and 10 physically active controls matched for age and weight were tested in a reaction and determination test requiring upper and lower extremity responses to visual and audio cues. Further tests comprised evaluation of one-leg postural stability on a two-dimensional moveable platform, measures of maximum strength performance capacity of the extensors of the leg on a leg press, and a test of force capacity of the arms in a sitting position at a steering wheel. An additional arm endurance test consisted of isometric work at the steering wheel at +30° and −30° where an eccentric threshold load of 30 N.m was applied. Subjects had to hold the end positions above this threshold until exhaustion. Univariate one way analysis of variance (α = 0.05) including a Bonferroni adjustment was used to detect group differences between the drivers and controls. Results: The reaction time of the racing drivers was significantly faster than the controls (p = 0.004). The following motor reaction time and reaction times in the multiple determination test did not differ between the groups. No significant differences (p>0.05) were found for postural stability, leg extensor strength, or arm strength and endurance. Conclusions: Racing drivers have faster reaction times than age-matched physically active controls. Further development of motor sport-specific test protocols is suggested. According to the requirements of motor racing, strength and sensorimotor performance capacity can potentially be improved.